Effect of Leadership Style on Employee Performance in Health Care Industry in India - Ameet Sao; Rachana Saxena; Chandrani Ganguly; Gautam S Bapat; Pooja Sharma (ACHSM, 2022)
Leadership is a vital component in increasing employee performance in business. Under leadership, personnel are led, inspired, assigned, and assisted in carrying out tasks efficiently. The present study aimed at examining the function and influence of leadership style on employee performance in the health care business in India. The researchers employed a questionnaire to collect primary data using a simple random sampling approach to fulfill the study objectives. The data demonstrated that transactional leadership, transformational leadership, and delegating leadership styles had a substantial influence on the employee performance in the health care business at (β= 0.42 p<0.005, β= 0.36 p<0.005, β= 0.38, p<0.005) accepting the hypothesis H1 (The effect of transformational leadership is positive on employee performance in health care institutions.), H2 (The effect of transactional leadership is positive on employee performance), and H5 (The effect of delegating leadership is positive on employee performance). *(The paper presented at the 7th International Conference on Embracing Change & Transformation Innovation and Creativity 26-28 May 2022)